2008
DOI: 10.1590/s0103-84782008000800003
|View full text |Cite
|
Sign up to set email alerts
|

Dinâmica populacional do psilídeo-de-concha Glycaspis brimblecombei (Moore, 1964) (Hemiptera: Psyllidae) e de seu parasitóide Psyllaephagus bliteus (Hymenoptera: Encyrtidae) em floresta de Eucalyptus camaldulensis

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 5 publications
1
16
1
3
Order By: Relevance
“…The results of the present study do not support, nor do they reject the influence of rainfall in psyllid abundance, presumably because there are no distinct periods of rainfall and drought in the study area. A similar situation was observed in other regions where the red gum lerp psyllid has spread (Ferreira Filho et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The results of the present study do not support, nor do they reject the influence of rainfall in psyllid abundance, presumably because there are no distinct periods of rainfall and drought in the study area. A similar situation was observed in other regions where the red gum lerp psyllid has spread (Ferreira Filho et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Climate conditions influence the growth rate; high temperatures without rainfall break down the populations, but are not enough to minimize damage. The effects of high temperatures were also evaluated in Brazil (Ferreira-Filho et al 2008), where no influence of rainfall was found on population dynamics, because, as pointed out by the authors, during the observations there were no distinct periods of rainfall and drought. Regarding the effects of the rainfall, Oliveira et al (2012), with an experimental test conducted on seedlings of E. camaldulensis, have proven the effects of artificial rain in reducing the abundance of lerps through solution and mechanical removal by water.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the developmental times decrease with increasing temperatures (Daane et al 2005;Ferreira-Filho et al 2008;Huerta et al 2010). In Italy the phenology, distribution and control capacity of the parasitoid are currently being studied.…”
Section: Discussionmentioning
confidence: 99%
“…Favaro (2006) studied the population dynamics of G. brimblecombei and found no correlation in the numbers of eggs and immatures with rainfall. In contrast , Ferreira Filho et al (2008) and also studied the population dynamics of the psyllids, found that there is direct relationship between decrease in rainfall and increase in populations of G. brimblecombei. Oliveira et al (2012), in studies with artificial rain, found that 2 days of rain are efficient to decrease more than 50% of the population of lerps with almost 100% efficiency after 5 days of rain.…”
Section: Discussionmentioning
confidence: 99%
“…Since the detection of G. brimblecombei in Brazil studies have been conducted on the biology (Ferreira et al, 2009;Firmino-Winckler et al, 2009;Wilcken et al, 2010), population dynamics (Ferreira Filho et al, 2008), influence of environmental factors (Silva et al, 2010;Oliveira et al, 2012), biological control (Santana et al, 2003;Wilcken et al, 2010) and plant resistance (Pitta et al, 2006;Huerta et al, 2010;Pereira et al, 2013;Camargo et al, 2014). Based on geographical records the potential distribution of G. brimblecombei was predicted with different models using bioclimatic variables (Queiroz et al, 2013).…”
Section: Introductionmentioning
confidence: 99%